Study development of Chitosan and NanoDot (CNDs) as chemosensors for contact oil damage detection rising electricity costs at home against leakage currents and current theft - Yenny Agnes Angela Turnip; Indri Dayana; Habib Satria; Moranain Mungkin (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
The research aims to Study development of chitosan and nanodot as chemosensor for contact oil damage of rising electricity costs at home against leakage currents and current theft. This study it can be concluded that the leakage current with applicable experiments in the field is to unplug all equipment connections to the plug, turn off all switches, record the meter on the KWh meter, leave it for 2 hours, record the KWh meter again, compare the first record with the second record, if there is a difference value between the first recording and the second recording then the leakage current is proven to occur.